Common X‐Chromosome Variants Are Associated with Parkinson Disease Risk. Issue 1 (6th March 2021) - Le Guen, Yann; Napolioni, Valerio; Belloy, Michael E.; Yu, Eric; Krohn, Lynne; Ruskey, Jennifer A.; Gan‐Or, Ziv; Kennedy, Gabriel; Eger, Sarah J.; Greicius, Michael D.
Abstract : Objective: The objective of this study was to identify genetic variants on the X‐chromosome associated with Parkinson disease (PD) risk. Methods: We performed an X‐chromosome–wide association study (XWAS) of PD risk by meta‐analyzing results from sex‐stratified analyses. To avoid spurious associations, we designed a specific harmonization pipeline for the X‐chromosome and focused on a European ancestry sample. We included 11, 142 cases, 280, 164 controls, and 5, 379 proxy cases, based on parental history of PD. Additionally, we tested the association of significant variants with (1) PD risk in an independent replication with 1, 561 cases and 2, 465 controls and (2) putamen volume in 33, 360 individuals from the UK Biobank. Results: In the discovery meta‐analysis, we identified rs7066890 (odds ratio [OR] = 1.10, 95% confidence interval [CI] = 1.06–1.14, p = 2.2 × 10 −9 ), intron of GPM6B, and rs28602900 (OR = 1.10, 95% CI = 1.07–1.14, p = 1.6 × 10 −8 ) in a high gene density region including RPL10, ATP6A1, FAM50A, and PLXNA3 . The rs28602900 association with PD was replicated (OR = 1.16, 95% CI = 1.03–1.30, p = 0.016) and shown to colocalize with a significant expression quantitative locus (eQTL) regulating RPL10 expression in the putamen and other brain tissues in the Genotype‐Tissue Expression Project. Additionally, the rs28602900 locus was found to be associated with reduced brain putamen volume. No results reached genome‐wide significance in the sex‐stratified analyses. Interpretation: We report the first XWAS of PD and identify 2 genome‐wide significant loci. The rs28602900 association was replicated in an independent PD dataset and showed concordant effects in its association with putamen volume. Critically, rs26802900 is a significant eQTL of RPL10 . These results support a role for ribosomal proteins in PD pathogenesis and show that the X‐chromosome contributes to PD genetic risk. ANN NEUROL 2021;90:22–34